The role of markup for enabling interoperability in health informatics - McKeever, Steve; Johnson, David (Frontiers in Physiology, 2015)
Interoperability is the faculty of making information systems work together. In this paper we will distinguish a number of different forms that interoperability can take and show how they are realised on a variety of physiological and health care use cases. The last fifteen years has seen the rise of very cheap digital storage both on and off cite. With the advent of the 'Internet of Things' people's expectations are for greater interconnectivity and seamless interoperability. The potential impact these technologies have on healthcare are dramatic: from improved diagnoses through immediate access to a patient's electronic health record, to 'in silico' modeling of organs and early stage drug trials, to predictive medicine based on top-down modeling of disease progression and treatment. We will begin by looking at the underlying technology, classify the various kinds of interoperability that exist in the field, and discuss how they are realised. We conclude with a discussion on future possibilities that big data and further standardizations will enable.